민간기업 조경공사에서 나타나는 식재설계 변경 타당성에 대한 전문가 인식 분석 - 박재영; Jae Young Park; 조세환; Se Hwan Cho (한국조경학회지, 2014)
본 연구는 민간기업에서 시행한 아파트 단지의 조경공사 중 식재설계변경의 유형과 변경의 타당성을 분석하여 공기업과 비교.고찰함으로써 조경공사 시에 발생하는 식재설계 변경을 객관적이고 효율적으로 관리하기 위한 기초 자료 제시를 목적으로 수행하였다. 본 연구의 결과 다음과 같은 다섯 가지를 얻을 수 있었다. 첫째, 민간기업에서 시행한 아파트 단지조경공사에서 발생한 설계 변경 중 식재공사에서 발생한 비율이 61.8%를 차지하고 있음으로써 식재 부분이 설계변경의 주된 대상이 되는 것으로 나타났다. 둘째, 이러한 설계변경원인으로는 주로 공기부족 등 현장 여건과 관련되는 것이었고, 특히 체계적 설계변경보다는 현장에서 구두 설계변경승인으로 이루어지는 것으로 나타났다. 셋째, 식재설계의 설계변경은한 건의 설계변경 승인에 7~48회의 동시다발적으로 발생하는 특징을 보이고 있었다. 넷째, 민간기업에서 발생하는 조경식 재공사 설계변경 유형은 ‘이용자를 고려한 설계변경’, ‘이미지 개선을 위한 설계변경’, ‘유지관리의 용이성을 위한 설계변경’, ‘설계내역 불일치로 인한 설계변경’, ‘타 공종과의 관계로 인한 설계변경’, ‘현장조사 미비로 인한 설계변경’, ‘시공성을 고려한 설계변경’ 등 총 7가지의 조경식재공사 설계변경 유형으로 구분할 수 있었는데 이것은 공기업에서 추진하는 설계변경 유형과 크게 다르지 않은 것으로 나타났다. 넷째, 이들 7가지 중 민간기업의 경우, ‘이용자를 고려한 설계변경’과 ‘이미지개선을 위한 설계변경’이 전체 설계변경의 빈도에서 과반수를 넘는 것으로 나타나 공기업의 ‘이용자를 고려한 설계변경’과 ‘설계내역 불일치로 인한 설계변경’으로 나타난 것과 상이한 점을 보이고 있었다. 다섯째, 식재공사 설계변경 과정의 경우 민간기업은 공기단축을 통한 공사비용 절감 차원에서 선(先)시공 후(後)승인의 관행을 보이고 있는 것으로 나타났지만, 공기업의 경우 현장에서 설계변경 사유가 발생하였을 시 현장 상황 및 변경내용을 검토하고 반영하여 설계변경 절차를 보이는 등 상이한 절차를 거치는 것으로 나타났다. 이상의 결과는 조경공사 중 식재설계 변경의 유형은 공기업, 사기업에 관계없이 7개의 범주로 설계변경의 유형은 동일하나, 설계변경의 주된 사유와 절차는 상이한 점이 있는 것으로 나타남으로써 식재설계 변경은 조경공사의 성격에 따라 합리성과 효율성 차원에서 유동성 있게 적용하는 것이 바람직한 것으로 사료되었다. This study analyzes the validity of the type classification of the type and design changes of apartment landscaping planting construction design changes that were completed in the private sector, efficiently manages the design changes that are displayed over landscaping planting work in general in the future, and performs research by placing the object underlying the presentation. The results are as follows. First, the percentage that occurred in the planting construction of design changes that have occurred in the apartment landscaping construction was carried out in the private sector and accounted for 61.8%. This indicates that part of the planting is a major design change. Second, as the cause of such a design change to be those associated with the field conditions such as lack of main construction period. In particular, due to a change in oral, appeared 7-48 times design changes of one review design change approval is complex, design changes of planting construction had shown a feature that occurs in multiple simultaneous. Third, the 7 types of Design Changes in planting design were delineated as ‘design changes for consideration of the user’, ‘design changes for image improvement’, ‘design changes for ease of maintenance’, ‘design changes due to the mismatch of design statement’, ‘design changes due to the relationship with the engineering species of other’, ‘design changes due to lack of field study’, and ‘design changes due to the consideration of feasibility.’ Fourth, ‘design changes for consideration of the user’ and ‘design changes for image improvement’ were found in more than half of the frequency of the overall changes. This differed from the results shown in public corporations. Fifth, if planting construction design change process, private companies, it was found that is showing the approval of the practice after the previous construction of the construction cost savings due to construction time. However, in the case of a public corporation, these exhibited a different aspect from the private sector and show a design change procedure that reflects the changes after the design change events in the field have occurred. The above results, the type of landscaping works in planting design change of public enterprises, regardless of the private sector, is the same in the seven types, the main reason of and procedures for design changes, indicating that there are other respects. In design change, it may be desirable to apply becomes liquidity rationality and efficiency of the dimension, depending on the nature of the landscape construction.